2002
DOI: 10.1080/09593332308618355
|View full text |Cite
|
Sign up to set email alerts
|

Biofiltration of Ammonia Gas with Sponge Cubes Coated with Mixtures of Activated Carbon and Zeolite

Abstract: Removal of ammonia gas was investigated using a biofilter system packed with small cubes of polyurethane sponge that were coated with a powder mixture of activated carbon and natural zeolite. Experimental tests and measurements include removal efficiency, pH, metabolic products of ammonia and kinetic analysis. A removal efficiency over 90% can be obtained with ammonia concentrations below 150 ppm and at contact times above 23 sec.The ammonia adsorbing power of the present biocarrier can protect the biofilter s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…NH 4 + and NO 2 − , which are the undissociated forms of NH 3 and HNO 2 , are common inhibitors of nitrifying bacteria. The results in this study are consistent with other findings [28,29]. NH 3 removal in a biotrickling filter is deteriorated due to the accumulation of NH 4 + and NO 2 − which induces inhibitory effects on both AOB (Nitrosomonas sp.)…”
Section: Continuous Operation Under Stepwise Increase Of Nh 3 Concentsupporting
confidence: 92%
“…NH 4 + and NO 2 − , which are the undissociated forms of NH 3 and HNO 2 , are common inhibitors of nitrifying bacteria. The results in this study are consistent with other findings [28,29]. NH 3 removal in a biotrickling filter is deteriorated due to the accumulation of NH 4 + and NO 2 − which induces inhibitory effects on both AOB (Nitrosomonas sp.)…”
Section: Continuous Operation Under Stepwise Increase Of Nh 3 Concentsupporting
confidence: 92%
“…However, more recently, Liang et al (2000) could obtain NH 3 removal effi ciencies of at least 95% at inlet concentrations between 20 ppmv and 500 ppmv in compost biofi lter in which active carbon was added to reduce compaction and channeling, as well as to increase the reactive surface and durability of the biofi lter. Similarly, removal effi ciencies over 90% were achieved by Kim et al (2002) at inlet concentrations up to 150 ppmv in a biofi lter system packed with small cubes of polyurethane sponge coated with a powder mixture of activated carbon and natural zeolite. Kalingan et al (2004) obtained complete NH 3 removal in a peat biofi lter containing inorganic supporting material at a NH 3 concentration of 200 ppmv, while Smet et al (2000) observed no NH 3 -toxicity in a compost biofi lter at concentrations up to 775 ppmv.…”
Section: Removal Of Ammoniamentioning
confidence: 96%
“…14) They used the Andrews-Haldane biokinetic model account for the inhibition effect of binary substrates in the biofiltration system. 39) In this work, we intended to treat a mixture of three substrates (NH 3 , H 2 S and toluene) using a mixture of microorganisms cultured in one single column: Thiobasillus thioparus, an autotroph, for the oxidation of H2S; Nitrosomonas and Nitrobactor, autotrophs, for the degradation of NH3; and Pseudomonas putida, a heterotroph for the oxidation of toluene. Then, competitive inhibition among the three substrates may exist in this system.…”
Section: Removal Efficienciesmentioning
confidence: 99%